Direct folding simulation of a long helix in explicit water - Zhang, John Z. H. (2013)
A recently proposed Polarizable Hydrogen Bond (PHB) method has been employed to simulate the folding of a 53 amino acid helix (PDB ID 2KHK) in explicit water. Under PHB simulation, starting from a fully extended structure, the peptide folds into the native state as confirmed by measured time evolutions of radius of gyration, root mean square deviation (RMSD), and native hydrogen bond. Free energy and cluster analysis show that the folded helix is thermally stable under the PHB model. Comparison of simulation results under, respectively, PHB and standard nonpolarizable force field demonstrates that polarization is critical for stable folding of this long α-helix.